2015
DOI: 10.1542/peds.2014-3667d
|View full text |Cite
|
Sign up to set email alerts
|

Early Screening of Autism Spectrum Disorder: Recommendations for Practice and Research

Abstract: This article reviews current evidence for autism spectrum disorder (ASD) screening based on peer-reviewed articles published to December 2013. Screening provides a standardized process to ensure that children are systematically monitored for early signs of ASD to promote earlier diagnosis. The current review indicates that screening in children aged 18 to 24 months can assist in early detection, consistent with current American Academy of Pediatrics' recommendations. We identify ASD-specific and broadband scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
189
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(198 citation statements)
references
References 105 publications
1
189
0
8
Order By: Relevance
“…1 With the advances reviewed by Zwaigenbaum et al 2,3 in this special issue of Pediatrics, and the growing evidence that ASD can be diagnosed accurately before 2 years of age, 4,5 the need for ASD treatment programs specifically designed for this age group has never been greater. Some authors have also argued that the second year of life is a particularly critical developmental period for children with ASD, for various reasons.…”
mentioning
confidence: 99%
“…1 With the advances reviewed by Zwaigenbaum et al 2,3 in this special issue of Pediatrics, and the growing evidence that ASD can be diagnosed accurately before 2 years of age, 4,5 the need for ASD treatment programs specifically designed for this age group has never been greater. Some authors have also argued that the second year of life is a particularly critical developmental period for children with ASD, for various reasons.…”
mentioning
confidence: 99%
“…8 Recent studies indicate that intensive behavioral therapy starting as early as 18 months of age is associated with decreases in core symptoms of ASD and improvement in cognition, language, and adaptive skills. 9,10 After diagnosis, children with ASD require ongoing care within a medical home to address associated medical conditions, coordinate care with specialists, and provide family support.…”
mentioning
confidence: 99%
“…• Evidence supporting this statement is summarized in Table 2 of the article by Zwaigenbaum et al 17 • Emerging data suggest that ASD diagnoses before 24 mo of age are stable, although further research is needed, particularly involving children identified via early screening 5.…”
Section: Discussionmentioning
confidence: 96%
“…To inform the work of each group, literature searches were conducted on Medline to identify relevant articles for each topic (the specific search terms are provided in the other articles in this supplement to Pediatrics [16][17][18] ). Search results were complemented by additional publications identified by working group members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation